Original Article Electrodiagnostic referrals at a tertiary center: Electrodiagnostic referrals at a tertiary center (Bombay Hospital Journal, 2024)
Introduction:Electrodiagnostic studies are used for the diagnosis of various lower motor neuron disorders. A set of necessary tests are performed for exact localization of disease. The aim of this study is to assess the frequency of the different lower motor neuron diseases and to see how many patients require follow up EDx studies for different conditions.Material and methodsThis is a retrospective study and data of consecutive patients assessed in our EDx laboratory in the years 2021 and 2022 were included. Data was included as number of cases with a final EDx diagnosis. Total number of cases of each type were entered month wise with the total number of cases of each EDx diagnosis as inferred after the test.Results:In the year 2021, a total of 2732 patients were tested for EMG and EPs in the EDx laboratory. In the year 2022, 3425 patients were tested. The maximum number of patients (905) had normal EDx findings. The most common abnormal diagnosis included traumatic nerve / plexus injuries (668), closely followed by upper / lower limb radiculopathies (645). Somatosensory evoked potential studies for assessing posterior column conduction defects formed the next large referral (598). 478 patients underwent follow up studies followed by Carpal tunnel syndrome (357) and Diabetic peripheral neuropathies (347). Also, a special mention of 130 cases of EMG guided laryngeal botulinum toxin injections for patients with spasmodic dysphonia where the injection is given by Laryngologist /Voice surgeon.Conclusion:To conclude, in our study, the order of electrodiagnostic outcome is normal study followed by peripheral neuropathies, followed by traumatic neuropathies / plexopathies and somatosensory evoked potential studies over the course of 2 years in a total of 6157 patients. Our study reports the maximum percentage of normal EDx findings as consistent with other studies. Most other studies have reported polyneuropathy, entrapment neuropathy, and disorders of the motor nerve root and plexus as the most common reasons for electrodiagnostic requests(19,20). The large number of SSEP referrals as in our laboratory, have not been studied at other centres as reviewed. The strength of our study  is 1) the large sample size even though the study has been done only at one centre, and, 2)  the maintenance of accurate records.